Men's knowledge, perception, attitude and practices related to family planning comparative study of Brgy. Veteran's Village and Brgy. Danao in Iloilo City. - Matiling, Lorraine Kier J.
This study aimed to determine and compare the knowledge, perception, attitude and practice of family planning of married men living in a barangay (Brgy. Veteran's Village, City Proper) which has a family planning program for the past 10 years, with those of married men living in a barangay (Brgy. Danao, City Proper) with no such program. Specifically, the researchers sought to determine and compare what do married men know about family planning, what is their perception towards family planning, the level of their attitude on family planning, and their family planning practices. Purposive sampling and lottery sampling were the samplimg techniques used by the proponents of this study. Purposive sampling was used to determine the two communities involved in the study. Lottery sampling on the other hand was used to determine the number of respondents , 198 married men were chosen as respondents in Brgy. Veterans Village and 66 were chosen in Brgy. Danao., Survey questionnaires were used to gather the needed relevant information to the study. Results of the study showed that in terms of their knowledge on family planning, majority of the respondents in both communities have common knowledge although there is a higher similarity among the respondents in Brgy. Veteran's Village compared to Brgy. Danao. For most of the respondents, family planning involves the use of contraception to limit childbirth. The majority of the respondents in Brgy. Veteran's Village perceived that family planning is not that important although they think that it is beneficial in terms of family's health. In Brgy. Danao, a high proportion of the respondents perceived family planning as important and beneficial. There is a high level attitude towards family planning found in both barangays. There is a higher percentage of respondents with high attitude level towards family planning in Brgy. Veteran's Village than in Brgy. Danao. The most common method of family planning practiced by men in both communities was the use of condoms, oral contraceptives, and IUDs. The knowledge, perception, attitude and practices of married men of brgy. Veteran's Village did not differgreatly from those of married men of Brgy. Danao, City Proper despite existence of a family planning program in the latter. The mere existence of a family planning program in a community will not solely affect men's knowledge, perception, attitude and practices of men; other factors are to be taken into consideration such as the agents of socialization particularly media and education. It is recommended that in secondary and in tertiary schools family planning, gender issues and reproductive health should be incorporated in absic health related subjects and appropriate social science courses. The use of media should be maximized in disseminating information about FP by program initiators. The dissemination of information should on a regular and consistent period. An assessment should be conducted on the effectivity of FP programs on an annual basis.